Answer:
48
Step-by-step explanation:
-2(1)^2(3(1)^2 – 7(1) + 10)
-2^2(3^2 – 7 + 10)
4(9 - 7 + 10)
4(12)
48
Each term is being divided by -3, so the next three terms would be:
-1/3, 1/9, -1/27
Answer:
See attached picture.
Step-by-step explanation:
Quadratic equation which has no solution gives zero for the value of d.
d = b² - 4ac
0 = 3² +- 4(-1)c
-9 = +_ 4c
c = -9/-4 pr 9/-4
c = 9/4 or -9/4
In short, Your Answers would be Option C & E
Hope this helps!
This is a system of equations. You can solve it by substitution or elimination. I'm going to use substitution x - 2y = -4.5; add 2y to each side x - 2y + 2y = -4.5 + 2y; simplify x = 2y - 4.5 2(2y - 4.5) + 3y = 12 4y - 9 + 3y = 12 7y - 9 = 12 7y - 9 + 9 = 12 + 9 7y = 21 y = 3 <--------first answer x - 2y = -4.5 x - 2(3) = -4.5 x - 6 = -4.5 x -6 + 6 = -4.5 + 6 x = 1.5 <--------second answer Check: 2(1.5) + 3(3) = 12? 3 + 9 = 12? 12 = 12; It checks 1.5 - 2(3) = -4.5? 1.5 - 6 = -4.5? -4.5 = -4.5; It checks x = 1.5 and y = 3 <-----------Final Answer